Long-term reliability of ImPACT in professional ice hockey. Issue 2 (17th February 2016) - Echemendia, Ruben J.; Bruce, Jared M.; Meeuwisse, Willem; Comper, Paul; Aubry, Mark; Hutchison, Michael
Abstract: Objective : This study sought to assess the test–retest reliability of Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) across 2–4 year time intervals and evaluate the utility of a newly proposed two-factor (Speed/Memory) model of ImPACT across multiple language versions.Method : Test–retest data were collected from non-concussed National Hockey League (NHL) players across 2-, 3-, and 4-year time intervals. The two-factor model was examined using different language versions (English, French, Czech, Swedish) of the test using a one-year interval, and across 2–4 year intervals using the English version of the test.Results : The two-factor Speed index improved reliability across multiple language versions of ImPACT. The Memory factor also improved but reliability remained below the traditional cutoff of .70 for use in clinical decision-making. ImPACT reliabilities remained low (below .70) regardless of whether the four-composite or the two-factor model was used across 2-, 3-, and 4-year time intervals.Conclusions : The two-factor approach increased ImPACT's one-year reliability over the traditional four-composite model among NHL players. The increased stability in test scores improves the test's ability to detect cognitive changes following injury, which increases the diagnostic utility of the test and allows for better return to play decision-making by reducing the risk of exposing an athlete to additional trauma while the brain may be at a heightened vulnerability to such trauma. Although the Speed Index increases the clinical utility of the test, the stability of the Memory index remains low. Irrespective of whether the two-factor or traditional four-composite approach is used, these data suggest that new baselines should occur on a yearly basis in order to maximize clinical utility.